A qualitative research on the grandparent-grandchild relationship ın the covid-19 pandemic - Eda Nazlı Gaspik; Rumeysa Çapuk; Zerrin Mercan (My University, 2023)
The study aims to examine the relationships of grandparents with their grandchildren in the Covid–19 pandemic. The phenomenological model and interview technique, one of the qualitative research designs, was used. The convenient/accidental sampling method, which is one of the non-random sampling methods, was used in the study. The study group of the research consists of 13 grandparents and 13 grandchildren who experienced the pandemic process in Gaziantep city center in 2020–2021. In the study, the "Grandparent Opinions Form for the Grandparent-Grandchild Relationship During the Pandemic Process", which was prepared to meet with grandparents, and children's pictures in which children's views took place were used as data collection tools. The data obtained from the children consists of 26 pictures. While 13 of the pictures reflect children's thoughts about the Covid–19 process, 13 of them reflect their relationship with their grandparents. Content analysis was performed on the obtained data. Based on the findings of the study, it was revealed that the Covid–19 pandemic negatively affected the relationship of grandparents with their grandchildren, children were negatively affected by the Covid–19 process, but their relationships with their grandparents were not affected in terms of their grandchildren.
Keywords: covid-19; pandemic; grandparent-grandchild communication; preschool period.child